Curcumin as an anti-arthritic agent in collagen-induced arthritic sprague-dawley rats - Zahidah, A.F; Faizah, O; Nur Aqilah, K; Taty Anna, K (Universiti Kebangsaan Malaysia, 2012)
Curcuma longa or turmeric has long been used in traditional medicine by the local population in Malaysia as an antiinflammatory agent. It has been proven to contain natural antiarthritic compound called curcumin. Joints abnormality and destruction have been implicated in the pathogenesis of rheumatoid arthritis (RA) due to inflammatory reactions. In this study, collagen-induced arthritis (CIA) model was utilized to study the effects of curcumin on joint inflammation in Sprague-Dawley rats. Body weight measurement, arthritis score assessment and radiology score assessment were carried out at specific intervals throughout this study. The results showed that the mean arthritis and radiology scores for animal groups designated as CIA CurcuminC and CIA CurcuminT were significantly lower compared with the negative control (CIA OV) group respectively. The mean arthritis scores for CIA CurcuminC group is significantly lower compared with CIA CurcuminT group but there is no significant difference in the mean radiology scores between the CIA CurcuminC and CIA CurcuminT groups. In conclusion, the oral supplementation of curcumin at the dose of 110 mg/mL/kg/day has a potential to delay and improve joint abnormality and injury in Sprague-Dawley rats with CIA.